Diseminasi Perangkat Pembelajaran dan Media Berbasis Cognitive Load Theory untuk Guru dan Siswa SMP di Sekolah Indonesia Kuala Lumpur - Natadiwijaya, Ismail Fikri; Anjarsari, Putri; Prasetyo, Zuhdan Kun (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Research on science learning with the Cognitive Load Theory (CLT) approach shows a positive impact on students, especially in reducing cognitive load and improving learning outcomes. The results of the preliminary study showed that teachers at Sekolah Indonesia Kuala Lumpur did not know much about what CLT is and how CLT-based devices and media are formed. Based on this, CLT is disseminated for teachers and students through workshop method. The results by the data show that this Community Service has a positive impact because students are enthusiastic, understand the lesson and all media products produced by teachers are proven to have implemented cognitive load theory through measurement based on product assessment rubrics. The scientific impact of this service activity is to enrich the application of  Cognitive load theory in the field, as well as provide feedback for curriculum development and learning methods. The recommendation for this activity is that similar activities need to be replicated in other areas with similar school characteristics so that the benefits can reach a wider audience.